2022
DOI: 10.1371/journal.pntd.0010527
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of simian malaria among macaques in Malaysia (2000–2021): A systematic review

Abstract: Background The aim of Malaysia to eliminate malaria nationwide by 2020 seems need to be prolonged. Whilst Malaysia has successfully eliminated human malaria transmission, simian malaria parasites such as Plasmodium knowlesi, P. cynomolgi, P. inui and P. cynomolgi are the emerging cause of malaria in humans. The epidemiological study of simian malaria in primates provides useful information in identifying the risk of human-macaques Plasmodium infection. Methodology/Principal findings This study was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 62 publications
(127 reference statements)
0
6
0
Order By: Relevance
“…The result of such recombination is the highly related clones observed in the NRAF plots, which most probably derive from the co-transmission of polyclonal infections originating in the macaque hosts. Being a natural reservoir for multiple zoonotic Plasmodium species, macaques have been shown to be co-infected with up to five simian Plasmodium species (44) and multiple P. knowlesi clones (46, 47). Alternatively, the isolates in which we see distinct clones are more likely to be examples of superinfections, as multiple clones originating from the same macaque host would have undergone recombination during reproduction in the mosquito host.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result of such recombination is the highly related clones observed in the NRAF plots, which most probably derive from the co-transmission of polyclonal infections originating in the macaque hosts. Being a natural reservoir for multiple zoonotic Plasmodium species, macaques have been shown to be co-infected with up to five simian Plasmodium species (44) and multiple P. knowlesi clones (46, 47). Alternatively, the isolates in which we see distinct clones are more likely to be examples of superinfections, as multiple clones originating from the same macaque host would have undergone recombination during reproduction in the mosquito host.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of apparent superinfections observed in Sabah is lower than frequencies observed in P. faciparum or P. vivax infections in moderate to high endemic settings (42, 43). However, it needs to be considered that the proportion of P. knowlesi superinfections described here is only reflective of the human host population and may be higher in the natural macaque hosts (44). Infection complexity in P. knowlesi is complicated by the zoonotic nature of P. knowlesi transmission, with multiple underlying parasite, host and epidemiological factors potentially influencing the establishment of successful erythrocytic replication of multiple inoculated P. knowlesi strains within humans causing symptomatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…In natural conditions, Pcy has been reported as mono-infections and/or mixed infections with other simian malaria parasites such as P. inui ( Pin ), P. coatneyi ( Pct ) and P. fieldi ( Pfld ) (Table 1 and Supplementary material 1). A recent systematic review reported an average Pcy prevalence of 33.05% in macaques from Malaysia [ 35 ]. In Philippines, the prevalence of Pcy was 23.2% in captive and wild M. fascicularis long-tailed monkeys [ 36 ].…”
Section: Epidemiology Of Natural P Cynomolgi Infec...mentioning
confidence: 99%
“…Malaria is a protozoan infectious disease caused by Plasmodium, which is transmitted through the bite of a female Anopheles mosquito (Mali et al, 2006;Sam et al, 2022). Plasmodium in humans infects erythrocytes and undergoes asexual development in liver tissue and erythrocytes.…”
Section: Introductionmentioning
confidence: 99%